Virtual Group Appointments Reduce Distress and Improve Care Management in Young Adults with Type 1 Diabetes. (November 2022) - Bisno, Daniel I.; Reid, Mark W.; Fogel, Jennifer L.; Pyatak, Elizabeth A.; Majidi, Shideh; Raymond, Jennifer K.
Purpose: The purpose of this study was to analyze the impact of virtual group appointments (VGA) on self-reported health-related outcomes and care activities for young adults (YA) with type 1 diabetes (T1D). Methods: Fifty-three YA (ages 18-25 years) with T1D participated in a randomized controlled trial (RCT) of the Colorado Young Adults with T1D (CoYoT1) Clinic intervention, encompassing telehealth (TH) with or without VGA. Both new patients ( n = 32) and those who participated in a pilot phase ( n = 26) were randomized to CoYoT1 Clinic (TH+VGA; n = 23) or TH-only ( n = 35) and followed for 1 year. YA completed the Diabetes Distress Scale (DDS), Diabetes Strengths and Resilience (D-STAR), Self-Efficacy in Diabetes (SED), Self-Management of Type 1 Diabetes in Adolescence (SMOD-A), Center for Epidemiologic Studies Depression (CES-D), and EuroQol (EQ-5D) scales at baseline and study end. Results: YA were 67% female, 84% white, 10% Latinx, and the mean age was 20.4 years old. At study end, participants in CoYoT1 Clinic reported significantly reduced diabetes distress compared to those in TH-only, who reported increased levels [Effect Size (ES) = −0.40, P = .02]. Specifically, CoYoT1 Clinic participants reported relative reductions in Physician (ES = −2.87, P = .02) and Regimen-related distress (ES = −0.35, P = .01). In addition, participants in CoYoT1 Clinic reported improved self-management of T1D-related problem solving (ES = 0.47, P = .051) and communication with care providers (ES = 0.39, P = .07). Conclusions: Virtual group attendance in CoYoT1 Clinic was associated with significant improvements in diabetes-related distress. Long-term exposure to VGA should be investigated in YA with T1D and other pediatric chronic conditions.